أبو البركات البلفيقي، قاضيا ومؤرخا وشاعرا ........................... Abu al-Barakat al-Balfiqi: Judge, Historian and Poet - مرسي شعبان محمد (الدراسات الإسلامية, 2018)
This article was originally written in Spanish by the late Spanish lady scholar Soledad Gibert Fenech. She was professor of Spanish literature at the University of Madrid in its Faculty of Arts. She died in 2007. Professor Shaban Muhammad Mursi of Egypt has translated this article from Spanish. The writer introduces in her article the versatile personality of Abu al-Barakat al-Balfiqi of the eighth/ Fourteenth century Muslim Spain who was at once a Judge, a historian and a renowned poet of Arabic. She traces his biographical details and academic ancestry from the earliest Arabic sources relating to Muslim Spain. The writer also introduces al-Balfiqi’s works and cites specimens of his Arabic poetry to highlight his literary genius.